The effect of medication safety education program on the knowledge, attitude and practices of registered nurses in a private hospital - Tajuddin, Nur Izzana Ahmad; Kunju, Annamma Kunju; Ahmad, Aini (JOURNAL OF Tropical Medicine Issues, 2025)
Background: Patient safety is crucial in healthcare, with medication being a key component in assessing quality. Medication errors, which are unintended issues in the drug administration process, can occur at any stage—prescribing, dispensing, storing, preparing, or administering and pose serious risks to patients. Defined as accidental failures in the drug-treatment process, these errors contribute significantly to preventable adverse events and public health burdens. Addressing medication errors requires a thorough and comprehensive approach to minimize their impact. Purpose: To assess and enhance nurses' understanding of medication errors, their causes, and preventive strategies through a comprehensive medication safety program. Method: A quantitative, single-group, non-randomized quasi-experimental design with pre- and post-tests. It involved 57 registered nurses from healthcare facilities. Data were collected before and after the program intervention using self-administered questionnaires and objective structured clinical examinations (OSCE). Analysis was performed using SPSS version 22. Results: Significant improvements in nurses' knowledge, attitudes, and practices regarding medication safety. The percentage of participants with "Very Good" knowledge increased from 0% before the program to 45.6% afterward, while those with poor knowledge decreased from 68.4% to 15.8%. Good attitudes dropped to 5% post-intervention, and the mean score for practices increased to 16.6667 following the program. Conclusion: The medication safety education program significantly enhanced nurses' Knowledge, Attitudes, and Practices (KAP), leading to a notable reduction in medication errors. The program fostered collaborative learning among healthcare personnel, improved patient outcomes, and increased nurses' confidence in medication administration. It also clarified roles within the healthcare team and promoted a culture of open communication and teamwork, which is vital for patient safety. Keywords: Interprofessional Education; KAP; Medication Safety; Registered Nurses; Patient Safety.